PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI KELAS VII-1 SMPN 25 PEKANBARU - Suparmi, Suparmi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This research focuses on an effort to look improvement of activities and a biology subject result as an effect of implemention of Numbered Head Together (NHT) in learning. This research was done at SMP N 25 Pekanbaru on biology subject, with subject was 40 students of class VII-1, 19 females and 21 males. After this research has been done, the average students’ activities increased on activity of listening teacher’s explanation from 90% in the first cycle into 94 % in the second cycle. Then it was a proof that learning biology process with using Cooperatif Learning Model Type Number Heads Together can increase students’ participantion in learning process on classroom discussion. Meanwhile, students’ result on Biology learning, Animal Classification, in class VII-1 on SMPN 25 Pekanbaru using Cooperative Learning Model Type Numbered Heads Together increased from first to second cycle. In can be seen from thoroughness percentage of students who achieved above school standar, KKM, namely 27 person (68%) on the first cycle and 34 person (85%) on the second cycle, or it increased 17%.Keywords: numbered heads together, learning activity, learning result.